Identify the cause of claims on construction contracts in the West Papua Provincial Government Area - Adonia Pasinggi; Manlian Ronald A. Simanjuntak (Jurnal Indonesia Sosial Teknologi, 2024)
Along with the development of the construction service industry today, which is increasingly complex, construction service actors must carry out better project management so that the planned design can be realised properly. Before carrying out a construction project, the parties will agree on a legal basis in the form of a letter of agreement or a contract. In the execution of construction contracts, sometimes there are differences in interpretation and other things that can cause claims or claims. The formulation of the problem in this study is what are the potential risk factors of claims on construction contracts, what are the variables of potential claim risk on construction contracts, what are the variables of claims-forming models, what are the causes of risks in model-forming variables and what are the improvement recommendations produced in this study. The data collection method for this questionnaire was obtained by distributing the questionnaire three times. The results to be achieved in this study are to be able to determine the potential risks of what factors and variables can cause construction claims (first questionnaire), find out the variables of the claim-forming model (second questionnaire), and find out the causes of risk in the model-forming variables (third questionnaire). By knowing the level of influence of factors and variables, conclusions can be drawn about what needs to be anticipated in construction claims. Thus, appropriate recommendations are given to the West Papua Provincial Government to regulate the articles in the contract in more detail to minimise the potential for construction claims